1996
DOI: 10.1148/radiology.201.1.8816553
|View full text |Cite
|
Sign up to set email alerts
|

Sublabral recess of the superior glenoid labrum: study of cadavers with conventional nonenhanced MR imaging, MR arthrography, anatomic dissection, and limited histologic examination.

Abstract: A sublabral recess is common in cadaveric shoulders and has an appearance similar to that of published examples of SLAP lesions. Histologic findings were consistent with normal anatomic structure rather than with acquired, posttraumatic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
2
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 0 publications
8
78
2
5
Order By: Relevance
“…In a cadaveric study in which CT arthrogram and MR imaging were compared with macroscopic dissection of the labrobicipital complex, Waldt et al (2006) observed significant variability in the attachment of the superior labrum to the glenoid and a sublabral recess in 74% of cases. Other studies have demonstrated similar findings in up to 73% of specimens (Smith et al, 1996;Harzmann et al, 2003). Smith et al (1996) described a classification system outlining the different degrees of extension of the sublabral recess, from its absence (type I) to extension over 5 mm medially (type 4).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…In a cadaveric study in which CT arthrogram and MR imaging were compared with macroscopic dissection of the labrobicipital complex, Waldt et al (2006) observed significant variability in the attachment of the superior labrum to the glenoid and a sublabral recess in 74% of cases. Other studies have demonstrated similar findings in up to 73% of specimens (Smith et al, 1996;Harzmann et al, 2003). Smith et al (1996) described a classification system outlining the different degrees of extension of the sublabral recess, from its absence (type I) to extension over 5 mm medially (type 4).…”
Section: Introductionsupporting
confidence: 55%
“…In this instance, the labrobicipital complex has been described as loosely attached to the glenoid rim in a fashion analogous to the lateral meniscus in the knee. There have been varying depths of medial extension of the cleft observed (Smith et al, 1996;Waldt et al, 2006). The incidence of this anatomical variation may be more common than previously thought (Smith et al, 1996;Kreitner et al, 1998;Waldt et al, 2006).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…2) The terms â€oe¿ sublabral foramen,― â€oe¿ sublabral hole' â€oe¿ sublabral sulcus' and â€oe¿ sublabral re cess―have been used interchangeably in the ra diology literatureto describe a normalanatomic variation of the anterosuperiorportion of the la brum [4]. We believe that these four terms are not the same and that their clarification is neces …”
Section: Buford Complex Sublabral Foramen and Sublabral Recessmentioning
confidence: 99%